PERBEDAAN HASIL BELAJAR SISWA DENGAN PENERAPAN MEDIA PEMBELAJARAN WORDWALL PADA MATA PELAJARAN PROJEK KREATIF DAN KEWIRAUSAHAAN PADA SALAH SATU SEKOLAH DI KOTA PEKANBARU - Ilfajri; Haryana, Gani; Rizka, Mifta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low student learning outcomes in the subject of Creative Project and Entrepreneurship at a vocational high school in Pekanbaru indicate the need for more varied instructional media to support active and interactive learning. This study was conducted to analyze the differences in students’ learning outcomes with the implementation of Wordwall as a learning medium in the Creative Project and Entrepreneurship subject at one vocational school in Pekanbaru. The research employed a quantitative approach with an experimental design. The sample consisted of 64 students selected through purposive sampling, comprising 27 students in the experimental class and 37 students in the control class. Data were collected through pre-tests, post-tests, and questionnaires. The results of the data analysis revealed a significant difference in learning outcomes between the experimental and control classes following the implementation of Wordwall, as indicated by the independent samples t-test result showing a Sig. (2-tailed) value of 0.001 < 0.05. The mean post-test score of the experimental class was 92.59, while that of the control class was 80.81. These findings demonstrate that the use of Wordwall as a learning medium significantly affects students’ learning outcomes. Therefore, Wordwall is considered a feasible and effective alternative instructional medium to enhance students’ learning outcomes.